Piezoelectric ceramic materials on transducer technology for energy harvesting: A review - Ogbonna, V. E.; Popoola, A. P. I.; Popoola, O. M. (Frontiers in Energy Research, 2022)
Recently, energy harvesting through the means of piezoelectric transducer technology has increasingly attracted the attention of engineers and scientist in producing/generating electricity for human consumption. However, understanding of piezoelectric materials for piezoelectric transducers device in energy harvesting remains important in today’s energy systems engineering. Thus, the present review study centered on piezoelectric materials better understanding of the properties of different piezoelectric material (ceramic) when placed under mechanical stress or vibration and electrical field during energy harvesting using transducer device. With the available literature, lead zirconate titanate material showed to be the most common piezoelectric material with high energy generating performance but possess more mechanical failure and also compromised in harsh environment compared to lead free piezoelectric material. As such, the authors concludes that lead free piezoelectric material, such as zinc oxide, barium titanate remains the best conducive piezoelectric material over lead zirconate titanate, which basically affects human environment due to its toxicity. Thus, to widen the use of lead free piezoelectric materials in energy harvesting owing to their improved properties and environmental friendly, the authors recommends further enhancement of the free lead piezoelectric material properties via nanodielectric fillers incorporations using spark plasma sintering technique.